#TITLE_ALTERNATIVE# - MARIA (NIM : 12209099), ELISABETH
Perforation has an important role in production engineering, in which perforation is the only way to establish communication between the wells that have been cased with reservoir. Vogel's IPR equation is very commonly used to estimate reservoir productivity of a well, but this equation was built for open hole completion wells. Therefore, the equation is not suitable for perforated wells. Finally, Perez and Kelkar derived ForcheimerÃ‚Â’s equation with a numerical approach for estimating value of pressure loss around the perforation and then simplify the numerical solution methods to practical use. In 1995, Mr. Pudjo Sukarno built IPR equation for perforated well in solution gas drive reservoir. However, the value of the maximum rate, that used to construct the dimensionless IPR curve in this equation, was the maximum rate at open hole conditions, not in the perforation condition. Therefore, this study will use the value of maximum liquid rate in perforation condition to construct new dimensionless IPR curve. This study was conducted to construct dimensionless IPR curve with several sensitivities, which are perforating gun, the SPF number, and also the ratio between the length of the perforated length of open hole zone. This study was limited to the assumption that the pressure loss around the perforation is caused by high-velocity flow and does not consider the formation damage effect made by the perforation process. Eventually, a new general equation for wells IPR heterogeneous solution gas drive reservoir perforation was built.